Improving Motivation And Learning Outcomes In Social Studies Through The Stad Type Cooperative Learning Model In Grade 7 Students Of Frater Don Bosco Tomohon Junior High School North Sulawesi Province - Jemmy Handry Fransisco Pandey; Theodorus Pangalila; Julien Biringan (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Motivation is one of the factors that influence students’ learning outcomes. With high learning motivation, it is expected that students will achieve better and more satisfactory results. One of the learning models that can be used to improve students’ motivation and learning outcomes is the cooperative learning model of the Student Teams Achievement Divisions. This study aims to improve students’ motivation and learning outcomes through the implementation of the cooperative learning model of the Student Teams Achievement Divisions type on the topic of social interaction. This model emphasizes cooperation in heterogeneous groups, where students help each other understand the material and are then evaluated individually to contribute to the group score. In this study, motivation and learning outcomes are considered successful if more than 80% of students show improvement (classical completeness). The data were obtained from motivation questionnaires and students’ learning achievement tests administered before and after the implementation of the Student Teams Achievement Divisions learning model at SMP Frater Don Bosco Tomohon North Sulawesi Province. The results show that the implementation of the Student Teams Achievement Divisions cooperative learning model was able to improve students’ learning motivation, with 77.8% of students showing improvement in cycle I, increasing to 85.2% in cycle II. In addition, students’ learning outcomes also showed significant improvement, as indicated by the increasing number of students achieving learning mastery in each cycle. A total of 23 out of 27 students (85.2%) experienced improvement after participating in the Student Teams Achievement Divisions learning model, which falls into the very high category on the topic of social interaction.